Effect of Enteral Formula on Blood Glucose Levels and Body Weight of Type 2 Diabetes Mellitus Patients - Novianti, Anugrah; Harna, Harna; Muhandiyah, Megi (PT FORMOSA CENDEKIA GLOBAL, 2025)
Patients with type 2 diabetes mellitus with complications such as stroke usually have difficulty eating so they are given enteral formula (FRS) or commercial formula (FK) to control blood glucose levels and avoid excessive weight loss. To determine the effect of enteral foods FRS and FK on blood glucose levels and body weight of type 2 DM patients at Tarakan Hospital. This research was a quasi-experimental study with a pre post test control group design using a sample of 40 patients who were divided into 2 groups. The control group was given FRS enteral food and the treatment group was given FK enteral food. The pretest data were obtained when the patient was admitted to the hospital and the posttest data were obtained after the patient had consumed enteral food for seven days. The results of the Wilcoxon and Dependent T-test found significant differences in blood glucose levels before and after consuming FRS enteral foods (p = 0.0001) and FK (p = 0.0001), the Mann-Whitney test results showed no. differences in blood glucose levels after ingestion of FRS and FK enteral foods (p = 0.117). Whereas for body weight before and after consuming enteral food FRS and FK, there was no significant difference (p = 0.401) (p = 0.773). Independent T-test results showed no difference in body weight after consumption of FRS and FK enteral foods (p = 0.871). FRS and FK enteral foods can affect the increase of blood glucose levels to normal blood glucose levels. However, after receiving FRS or FK enteral food there was no change in body weight.